Hubungan Dukungan Keluarga dengan Adversity Quotient (Daya Juang) pada Ibu Yang Memiliki Anak Autis di SLB Kota Bukittinggi - Nengsih, Lidya; Fikry, Zulian (Indo-MathEdu Intellectuals Journal, 2024)
This study aims to see the relationship between family support and adversity quotient in mothers who have autistic children in SLB Bukittinggi city. This study uses a correlational quantitative method. The research sample consisted of 119 mothers who had autistic children at SLB Bukittinggi city who were selected through the quota sampling technique. This study is a modification of the adversity quotient measuring instrument (Ummah, 2021) and used the family support measuring instrument (Kismawati, 2019) which have reliability of 0.881 and 0.894, respectively. The results of spearman correlation r = 0.595 and p value = 0.000 (p<0.05) showed a significant positive relationship between family support and adversity quotient in mothers who have autistic children in SLB Bukittinggi city